(untitled) - Walter Benjamin (New York, 1968)
The book includes Benjamin's views on Kafka, Beaudelaire, Proust, Leskov, Brecht's Epic Theater, the Task of the Translator, the Work of Art in the Age of Mechanical Reproduction.
Keywords: literature - collections